Description of a new species of Marphysa Quatrefages, 1865 (Polychaeta: Eunicidae) from the west coast of Peninsular Malaysia and comparisons with species from Marphysa group A from the Indo-West Pacific and Indian Ocean - Idris, Izwandy; Hutchings, Patricia A.; Arshad, Aziz (Museum Victoria, 2014)
A new species of Marphysa Quatrefages, 1865 (Polychaeta: Eunicidae) is described from the west coast of Peninsular Malaysia and compared with species from Marphysa Group A from the Indo-West Pacific and Indian Ocean. The number of species known within Marphysa Group A has been increased, and the concept that M. mossambica is a widely distributed species in the Indo-Pacific is refuted. The new species is commercially important and occurs in the mangrove forest along the west coast of Peninsular Malaysia. Notes on the biology, ecology and commercial aspects of M. moribidii sp. nov. are presented.